The semantic guidance of fronting and delaying in verses with similar wording according to Badr al-Din Ibn Jama’ah (d. 733 AH) in his book (Unveiling the Meanings in the Similarities of the Mathani) - Ahmed, Dler Abdalla; Karim, Hiwa Abdalla (Sulaimani Journal for Humanities, 2019)
In Arabic language, changing the position of linguistic elements- pre and post mentioning, creates different semantic senses. In Holy Quran, this subject appears more concisely and precisely, especially, in resembling verses of Quran. In this research, the semantic differences of these verses which, a great scientist ( Badr Al-din bn Jamaha) has worked on it, have been illustrated as descriptive analysis. The research is comprised of an introduction, theoretical frame and two parts. In the first part, the semantic differences of nouns, pre and post elements which have been joined through linking devices, have been explained. The second part is concerned with, the semantic differences due to pre and post nouns and adjectives have been demonstrated in a way linguistic elements have previously been mentioned in a verse of Quran while, afterwards in others. Finally, the most important results have been displayed.